2019
DOI: 10.1111/cns.13098
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary evidence about irritability in patients with epilepsy treated by perampanel as first add‐on therapy compared to levetiracetam and valproic acid

Abstract: Summary Aims Irritability has been described as a frequent adverse event in patients affected by epilepsy and treated with perampanel (PER), levetiracetam (LEV), and less frequently with valproic acid (VPA). Since the questionnaire for irritability (I‐EPI) is a validated instrument to measure this psychiatric manifestation in patients affected by epilepsy, in this study we aimed at investigating the effect of PER as first add‐on therapy on I‐EPI. Moreover, we compared the effectivenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…PER did not increase depression and anxiety scores-even when scores indicated a mild level of anxiety before PER treatment. Although irritability was often reported in PER RCTs and observational studies, this study reports no increase in irritability, in line with the results of another smaller cohort (222). However, another study on 136 patients found that irritability and depression comorbidities before PER administration (as well as etiology of structural abnormalities and concomitant use of nitrazepam) were associated with psychiatric and behavioral deterioration after starting PER treatment (223).…”
Section: Overview Of Per and Psychiatric Comorbidities In Epilepsysupporting
confidence: 86%
“…PER did not increase depression and anxiety scores-even when scores indicated a mild level of anxiety before PER treatment. Although irritability was often reported in PER RCTs and observational studies, this study reports no increase in irritability, in line with the results of another smaller cohort (222). However, another study on 136 patients found that irritability and depression comorbidities before PER administration (as well as etiology of structural abnormalities and concomitant use of nitrazepam) were associated with psychiatric and behavioral deterioration after starting PER treatment (223).…”
Section: Overview Of Per and Psychiatric Comorbidities In Epilepsysupporting
confidence: 86%
“…6 Perampanel (PER) is a third-generation ASM, licensed for the treatment of focal and generalized epilepsies and recognized as an effective therapy in particular when used as first add-on ASM. 7-11 Consistently, long-term adjunctive treatment with PER does not have any significant overall effects on global cognition in adolescent and adult patients. 12,13 Quantitative EEG (qEEG) is a technique used to evaluate brain background activity in patients affected by epilepsy and can represent a useful tool in order to monitor cognition.…”
Section: Introductionmentioning
confidence: 84%
“…Several studies investigating PER as an early or first add-on therapy in clinical practice were included in the PERMIT study ( 40 48 ). However, since the PERMIT study was conducted, several other studies of PER as first add-on therapy have been conducted, in both the clinical trial and clinical practice settings.…”
Section: Discussionmentioning
confidence: 99%